Feasability study on maize husk as resource for a novel composite material - Ruiz Trejo, Citlalli Elizabeth (Cranfield University, 2018)
Over the past decades, a dramatic increment on the production of maize husk (MH) in Mexico has been observed. Encouraging the study of this copious material as an alternative for the manufacture of composite materials, thereby enabling the use of MH. Offering advantages such as availability, renewability and more importantly the possibility to reduce local pollution levels without compromising the environmental integrity. The purpose of this research was to develop a maize husk-based composite (MHC) at a lab scale through a transdisciplinary systemic design approach (SDA). The SDA framework was developed from a designer point of view to confront the concerns of MH overproduction, including social, environmental, technical and economic implications. The investigated fibres were obtained from two harvesting methods: manual (MASH) and mechanical (ASPROS). Both MHF’s performance was lower than other natural fibres. ASPROS fibres showed a steadier mechanical performance with a cross-section area of 0.14 mm², an ultimate tensile strength of 45.75 MPa, a 7.65 % of elongation and Young’s modulus of 1.95 MPa. Nineteen different MHC blends were manufactured, at a concentration of 70/30 MH/binder. Four MH sizes with three binding systems were tested; the sizes were (1) whole husk, (2) chopped, (3) milled and (4) 10 % NaOH alkalinised fibres. The binding systems included: (A) a board made rearranging MH’s natural components through thermal fusion, (B) MH mixed with lignin for the production of non-resin MHC boards, and (C) MH blended with a super SAP® CPM epoxy resin (SSE). The sizereduction (milled and alkali) improved MHF’ surface interfacial bonding with SSE resin, however, only alkali treated presented enhanced tensile properties. Overall, the M30 boards met the properties of general purpose fibreboards for use under humid conditions (BS EN622-5:2009). The AK30 and M20 boards properties remained within the general-purpose fibreboards for use in dry conditions (BS EN622-5:2009).
Keywords: Agro-waste; maize husk; non-wood fibreboard; mechanical properties; physical properties; natural fibres; bio-based material; system design; sustainable innovation